Mubadalah in Fulfilling the Rights and Obligations of Contemporary Husbands and Wives - Bunyamin, Mahmudin; Nurjanah, Siti; Hermanto, Agus; Santoso, Rudi; Rochmad, Rochmad (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
The man is the head of the household, and the wife is the housewife. That is the paradigm embedded in our society in general, because so far men have always been the main ones at the forefront while wives have always been in a limited area. The problem is that contextually, the role of women is no longer in the domestic area alone, but many have also played a role outside the home to help their husbands earn a living. The question is how can the rights and obligations of husband and wife be exercised in this context? The purpose of this research is to obtain a reconstruction of new rights and obligations that are based on fikih mubadalah. This research is a literature review, qualitative type with a mubadalah approach. The result of this research is that the partners between men and women in realising justice in the household must be equal, such as mutual deliberation, mutual democracy and mutual kindness in relationships.